Hydrothermal Synthesis of Potassium Hexatitanates under subcritical and supercritical water conditions and its application in Photocatalysis - Rosiyah Binti, Yahya; Hayashi, H.; Nagase, T.; Ebina, T.; Onodera, Y.; Saitoh, N. (2001)
Hydrothermal synthesis of potassium hexatitanate was carried out under various subcritical and supercritical water conditions using potassium hydroxide and titanium tetraisopropoxide as starting materials. Characterization of these hydrothermally synthesized potassium hexatitanates by XRD, SEM, TEM, and thermal analysis showed that long, felted-like fibers of potassium hexatitanates were formed and these fibers are thermally stable up to 1273 K. The use of these fibers as photocatalysts in water decomposition was investigated using ruthenium oxide as the catalytic active phase. Photocatalytic activitiy in the water decomposition reaction was found to be much higher in comparison with the solid state synthesized photocatalyst. Activites of more than 13-fold were obtained for the photocatalysts synthesized under subcritical water conditions and between 27- and 59-fold for those synthesized under supercritical water conditions for water decomposition.